Le pittoresque et la couleur locale dans Le Voyage vers les Pyrénées de Victor Hugo - Martonyi, Éva (Verbum – Analecta Neolatina, 2003)
Victor Hugo wrote Le Voyage Vers les Pyrénées in 1843, during his travel in Spain. This work is analysed by the author from several aspects. First, taking the ancient archetypes of travelogue and story-telling as points of departure, the author discusses the characteristics of the genre in the 19th century. Then she goes on and inserts the work in the process of paradigm change typical of the century, when the notions 'pittoresque', 'couleur locale' and 'the exotic' were all present in the texts; nevertheless, the emphasis was increasingly shifted towards the need for presenting reality. Basing her arguments on quotes, the author argues that in the case of Victor Hugo, the notions mentioned basically have the same workings in travelogues written in prose as well as in poems.